Implementation of Design Thinking Concepts in Eco-Fashion Product Design - Gunawan, Arien Arianti; Putri, Mediany Kriseka; S. Putri, Ifa Nadhifah (Jurnal Manajemen Indonesia, 2023)
The study aims to determine how green design thinking and entrepreneurship concepts can be applied to fashion products made from recycled materials. This study uses a design thinking approach and a qualitative approach that aims to gain a deep understanding, develop theoretical foundations, and describe the reality of the research scope. The technique is in the form of collecting data from waste banks, garbage collectors, and several people who are competent in the fashion sector by conducting in-depth interviews. The combination of design thinking and green entrepreneurship can have a positive impact; problem-solving can be done through the design thinking stage to innovate in business while supporting the environmentally friendly movement. Products derived from "waste" generated by household consumption can be processed in such a way as to create selling value and be accepted by the community. Further research should consider seeking as many sources of information as possible, using appropriate tools, and studying every detail of the materials used. The findings of this study provide important insights into knowledge about design thinking and green entrepreneurship, as well as for those involved in product manufacturing. This research can also be a helpful tool in implementing knowledge about design thinking, green entrepreneurship, and the fashion sector. Keywords—Design Thinking; Eco-Fashion; Green Entrepreneurship